Peranan Bahasa Arab dalam Pengembangan Peradaban Islam - Gusti Tahir (Universitas Islam Negeri Alauddin, 2012)
Arabic language is a language used in al-Quran, thus, it is always used in ritual worship by all moslems throught out the world. For al-Quran is considered as the way of life, Arabic also functions as remainding language. In 1973, Arabic language was officially used in United Nation Organization. Not only is it as religious language, but it is as civilization language as well. Due to its functions, Arabian scientist have developed it as they have got some experiences from the great civilized countries. On their efforts, there had been some books or references translated into Arabic language, and thus broadened worldview of Arabians. In Indonesia, Arabic developes in line with Islamic progress. Arabic is used/spoken in ulama community, boarding school, religious school, even it was integrated in Indonesian language at least in vocabulary building